A Closed-Loop Optogenetic Platform - Firfilionis, Dimitrios; Hutchings, Frances; Tamadoni, Reza; Walsh, Darren; Turnbull, Mark; Escobedo-Cousin, Enrique; Bailey, Richard G.; Gausden, Johannes; Patel, Aaliyah; Haci, Dorian; Liu, Yan; LeBeau, Fiona E. N.; et al. (Frontiers in Neuroscience, 2021)
Neuromodulation is a potential treatment for numerous neurological conditions, but to expandthe therapeutic scope there is a need to improve the spatial, temporal and cell-type specificity ofstimulation. Optogenetics is a promising area of current research, enabling optical stimulation ofgenetically-defined cell types without interfering with concurrent electrical recording for closed-loop control of neural activity. We are developing an open-source system to provide a platform forclosed-loop optogenetic neuromodulation, incorporating custom integrated circuitry for recordingand stimulation, real-time closed-loop algorithms running on a microcontroller and experimentalcontrol via a PC interface. We include commercial components to validate performance, with theultimate aim of developing a fully-implanted system suitable for use in humans. In the meantimeour system is flexible and expandable for use in a variety of neuroscientific applications. Theplatform consists of a Controlling Abnormal Network Dynamics using Optogenetics (CANDO)Control System (CS) that interfaces with up to four CANDO headstages responsible for electricalrecording and optical stimulation through custom CANDO LED optrodes. Control of the hardware,inbuilt algorithms and data acquisition is enabled via the CANDO GUI (Graphical User Interface). Here we describe the design and implementation of this system, and demonstrate how it can beused to modulate neuronal oscillationsin vitroandin vivo.